Kluver–Bucy syndrome in one case with systemic lupus erythematosus - Hsiu-Fen Lin; Yi-Chun Yeh; Chien-Fu Chen; Wei-Chen Chang; Cheng-Sheng Chen; 林秀芬; 葉怡君; 陳建甫; 張瑋真; 陳正生 (Kaohsiung Journal of Medical Sciences, 2011)
Kluver–Bucy syndrome (KBS) is a collection of neuropsychiatric symptoms, including visual agnosia (prosopagnosia), hypermetamorphosis, placidity, hypersexuality, and hyperorality. Although neuropsychiatric manifestation is prevalent in cases with systemic lupus erythematosus (SLE), only one literature reported a case with SLE that had KBS previously. In this article, a 37-year-old woman with SLE who developed KBS and other neuropsychiatric symptoms is presented. Brain imaging proved the relevant structural lesion. The possible explanation of pathogenesis of KBS in SLE is discussed.